Drying of food products under inert atmosphere using heat pump - Hawlader, Mohammad Nurul Alam (2012)

(untitled)
In conventional drying of food products, the drying medium is air and the drying potential is controlled with the variation temperature. Normally, the drying is carried out at high temperature and the presence of oxygen in the air affects nutrients of the food product. To improve the drying potential and also to carry out the drying under low temperature conditions, a heat pump is used to improve the drying environment. Since the heat pump is operated in a closed loop, where condenser heat controls the drying temperature and evaporator removes the moisture content released at the drying chamber, the drying medium operates at low temperature and moisture content. As the system operates under closed loop condition, to eliminate the effect of oxygen in the air, the air is replaced by inert gases such as nitrogen and carbon dioxide. This paper includes results of drying of some heat sensitive fruit materials e.g. guava and papaya using nitrogen, carbon dioxide, and air to find the impact on nutrients and color. These results were also compared with those dried by freeze and vacuum dryers.